2019
DOI: 10.1186/s12958-019-0539-y
|View full text |Cite
|
Sign up to set email alerts
|

In rats with estradiol valerate-induced polycystic ovary syndrome, the acute blockade of ovarian β-adrenoreceptors improve ovulation

Abstract: BackgroundPolycystic ovary syndrome is characterized by hyperactivity of the ovarian sympathetic nervous system, increases in the content and release of norepinephrine, as well as decreases in the number of β-adrenoreceptors. In the present study, β-adrenoreceptors in the ovaries of rats with polycystic ovary syndrome were blocked and analyzed the resultant effects on ovulation, hormone secretion and the enzymes responsible for the synthesis of catecholamines.MethodsAt 60 days of age, vehicle or estradiol vale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…On the other hand, according to the inflammation hypothesis, the ovulation-related events have been reported to resemble an inflammatory reaction that accompany with leukocytes infiltration and production of inflammatory mediators like cytokines, vascular endothelial growth factor (Vascular Endothelial Growth Factor, VEGF), prostaglandins, and intracellular signaling pathways closely associated with inflammatory reaction [ 75 ]. Regarding the results shown in Table 1 , the laying hens, supplemented by BAA Salmeterol and BB Propranolol, significantly indicated more ovulation rate and the similar follicle size F1 to F5 as compared to control that was in agreement with the studies which showed catecholamines and Propranolol improve the ovulation rate and follicular development [ 76 , 77 ]. Besides, Fig.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, according to the inflammation hypothesis, the ovulation-related events have been reported to resemble an inflammatory reaction that accompany with leukocytes infiltration and production of inflammatory mediators like cytokines, vascular endothelial growth factor (Vascular Endothelial Growth Factor, VEGF), prostaglandins, and intracellular signaling pathways closely associated with inflammatory reaction [ 75 ]. Regarding the results shown in Table 1 , the laying hens, supplemented by BAA Salmeterol and BB Propranolol, significantly indicated more ovulation rate and the similar follicle size F1 to F5 as compared to control that was in agreement with the studies which showed catecholamines and Propranolol improve the ovulation rate and follicular development [ 76 , 77 ]. Besides, Fig.…”
Section: Discussionsupporting
confidence: 87%
“…An experimental study conducted by Pournaderi et al [ 40 ] found the same results, indicating that after EV-induced PCOS, the animals presented decreased levels of LH, FSH, and estradiol and also found increased levels of progesterone in comparison with the control group. Venegas et al [ 41 ] similarly found that increased serum levels of progesterone. Laird et al [ 42 ], in an in vitro study, examined the role of testosterone on the transition of preantral follicles to the antral form.…”
Section: Discussionmentioning
confidence: 99%
“…The first ten animals were left without PCOS induction and were treated for 20 days with a normal saline. The rest thirty females were given a single intramuscular injection of 4 mg estrogen valerate (Riedeldehaen, Germany) to induce PCOS [9][10]. After 30 days of induction of PCOS, the animals were divided into three groups (10 each) and treated respectively with cyproterone 12 mg/ kg, metformin 50 mg/kg as a single oral dose daily, while the third group was given normal saline (the vehicle) 0.5 ml/animal to serve as negative control (PCO untreated group).…”
Section: Methodsmentioning
confidence: 99%